RANCANGAN PERBAIKAN SISTEM KERJA BERDASARKAN KRITERIA 5S PADA INDUSTRI RUMAH TANGGA SEPATU - Yanti Sri Rejeki; Eri Achiraeniwati; Nur Rahman As’ad; Ricky Gunawan (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Cibaduyut is a shoe industry center area, located in Bandung city, West Java. This industry is required to be able to improve productivity and quality assurance of footwear produced to be able to compete with other similar companies. Generally, based on observations in previous research, the condition of the craftsmen works with simple equipment in a work environment that does not meet the requirements of an ergonomic working system that meets the requirements of effective, convenient, safe, healthy and efficient. Several improvements have been made to improving facilities, environments and working methods. These improvements still seem less effective and efficient because the work culture is still irregular. Based on the above, it is necessary to improve the work culture with the 5S method in every work station / process thoroughly and systematically so as to form a good working moral movement through the process of education, forming habits, discipline and building mindset of workers who support productivity effective, comfortable, safe, healthy and efficient, so that Cibaduyut shoe will able to compete in the future.